Perception of Corruption and the Relationship With Other Variables - Bozdo, Rejla (Archives of Business Research, 2022)
People perceive corruption at a rate that might not always be concurrent with the level of real corruption. Despite the fact, research on perception can help governments and other institutions better understand how to deal with the problem. This paper addresses the perception of corruption and its relationship with other variables of daily life, such as perception of the economy, education, health, security and politics in general, thus to investigate at what level the perception of corruption relates with or impacts the expectations and trust in other areas. The 369 respondents in the dataset, used for the analysis, live in Albania and have a mean age of 34.57 years old. Albania’s Corruption Index of Transparency International increased during 2020 by five points compared to 2013. 2020, this is at the level of 36 points, ranked 104th . While in 2013, it was 31 points.